Design, Synthesis, In Vitro and In Silico Studies of New Thiazolylhydrazine-Piperazine Derivatives as Selective MAO-A Inhibitors - Begüm Nurpelin Sağlık; Osman Cebeci; Ulviye Acar Çevik; Derya Osmaniye; Serkan Levent; Betül Kaya Çavuşoğlu; Sinem Ilgın; Yusuf Özkay; Zafer Asım Kaplancıklı (Molecules, 2020)
Monoamine oxidase (MAO) isoenzymes are very important drug targets among neurological disorders. Herein, novel series of thiazolylhydrazine-piperazine derivatives were designed, synthesized and evaluated for their MAO-A and -B inhibitory activity. The structures of the synthesized compounds were assigned using different spectroscopic techniques such as 1H-NMR, 13C-NMR and HRMS. Moreover, the prediction of ADME (Absorption, Distribution, Metabolism, Elimination) parameters for all of the compounds were performed using in silico method. According to the enzyme inhibition results, the synthesized compounds showed the selectivity against MAO-A enzyme inhibition. Compounds 3c, 3d and 3e displayed significant MAO-A inhibition potencies. Among them, compound 3e was found to be the most effective derivative with an IC50 value of 0.057 ± 0.002 µM. Moreover, it was seen that this compound has a more potent inhibition profile than the reference inhibitors moclobemide (IC50 = 6.061 ± 0.262 µM) and clorgiline (IC50 = 0.062 ± 0.002 µM). In addition, the enzyme kinetics were performed for compound 3e and it was determined that this compound had a competitive and reversible inhibition type. Molecular modeling studies aided in the understanding of the interaction modes between this compound and MAO-A. It was found that compound 3e had significant and important binding property.